Large reductions In amenable mortality associated with Brazil's primary care expansion and strong health governance - Hone,T; Rasella,D; Barreto,M; Atun,R; Majeed,A; Millett,C (Health Affairs, 2017)
Strong health governance is key to universal health coverage. However, the relationship between governance and health system performance is underexplored. We investigated whether expansion of the Brazilian Estratégia de Saúde da Família (ESF; family health strategy), a community-based primary care program, reduced amenable mortality (mortality avoidable with timely and effective health care) and whether this association varied by municipal health governance. Fixed-effects longitudinal regression models were used to identify the relationship between ESF coverage and amenable mortality rates in 1,622 municipalities in Brazil over the period 2000-12. Municipal health governance was measured using indicators from a public administration survey, and the resulting scores were used in interactions. Overall, increasing ESF coverage from 0 percent to 100 percent was associated with a reduction of 6.8 percent in rates of amenable mortality, compared with no increase in ESF coverage. The reductions were 11.0 percent for municipalities with the highest governance scores and 4.3 percent for those with the lowest scores. These findings suggest that strengthening local health governance may be vital for improving health services effectiveness and health outcomes in decentralized health systems.